New Palaeogene horntail wasps (Hymenoptera, Siricidae) and a discussion of their fossil record - Wedmann, Sonja; Pouillon, Jean-Marc; Nel, André (Zootaxa, 2014)
The phylogenetic placement of siricid hymenopterans and especially the relationships among Siricidae are not resolved, and are in need of further investigation. The fossil record helps to illuminate the evolutionary history of this group. In this paper, Xoanon? eocenicus sp. nov. is newly described from the Eocene Fossillagerstätte Grube Messel (Germany). Although several characters of the wing venation of this fossil are similar to the extant genus Xoanon, there remain some doubts concerning the generic placement. A newly found fossil is attributed to Urocerus ligniticus (Piton, 1940) from the Paloecene Fossillagerstätte Menat (France) and provides more morphological information on this species. An overview of the fossil record of Siricidae in the strict sense is given and the state of knowledge on the different fossils is reviewed.